Analysis of Science Learning Local Context (SeLoC) with Entrepreneurship Orientation for Life-Long Learning of Junior High School Students - Lipikuni, Hilary Fridolin; Henukh, Anderias; Benu, Rince Sefriana Margarita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to explore how the implementation of Science Learning Local Context (SeLoC) with an entrepreneurial orientation can support the development of lifelong learning (LLL) skills in junior high school students. The study used a descriptive method with a mixed methods approach. This study involved 10 schools in Kupang as well as 20 science teachers and 200 students/ Instruments used included questionnaires, in-depth interviews, and observations. Data were collected through interviews with teachers and students, observations of the implementation of SeLoC in class, and questionnaires to measure student and teacher perceptions. Qualitative data analysis was carried out thematically to identify patterns of student engagement and entrepreneurship integration, while quantitative data were analyzed using descriptive statistics. The results of interviews with teachers showed that SeLoC integration was viewed positively because it was able to improve practical skills and student engagement in science learning. However, the implementation of SeLoC is still limited to extracurricular projects. From the results of student interviews, they felt more interested in science learning that was relevant to everyday life. Observations revealed that SeLoC had not been fully integrated into the formal curriculum. The results of the questionnaire showed the majority of respondents (50%) agreed that SeLoC encourages innovation in learning, 45% agreed that science results can be used for new products, and 50% agreed that SeLoC develops an entrepreneurial and ethical mindset. In lifelong learning skills, 45% of respondents agreed that science learning supports learning continuity and increases adaptation and motivation, and 40% agreed that it supports independent learning. This study recommends further development of the SeLoC curriculum and specific training for teachers.Keywords:science learning, local context, entrepreneurship, life-long learning